The Urgency of Legal Protection for Weak Parties in Contemporary Contract Law - Dewi, Candra; Lestari, Indah; Nurjanah, Siti (Sahabat Publikasi, 2025)
Contemporary contractual relations in Indonesia are marred by structural inequalities, where powerful entities exploit vulnerable parties (consumers, workers, MSMEs) through standard form contracts, undermining the Civil Code’s principle of freedom of contract. Despite legal protections (e.g., Consumer Protection Law, Labor Law), weak enforcement and low awareness perpetuate injustice. This study examines the urgency of legal protection for weak parties, evaluates existing frameworks, and proposes reforms grounded in dignity justice to align contract law with social equity. A qualitative, normative-juridical approach analyzes legislation, jurisprudence (e.g., Supreme Court rulings), and scholarly theories. Exploitative clauses persist due to imbalanced bargaining power, but progressive judicial interpretation (ex aequo et bono) and dignity justice can mitigate inequities. The study advocates for legislative reforms, technological solutions (e.g., AI-assisted aid), and enhanced judicial training to ensure substantive justice, offering a blueprint for equitable contract law in Indonesia’s digital economy.